Library RelationAlgebra.regex


regex: the (flat) model of regular expressions


Require Import syntax kleene boolean lang lset sums normalisation.
Set Implicit Arguments.

We consider regular expressions over the alphabet of positive numbers
(It would be nicer to keep the alphabet as a parameter, since we need to instantiate it with a more structured type in kat_completeness; it's however realy painful to do so, since this model is used thoroughly through several files (rmx, nfa, ka_completeness) and this would prevent us from using modules to structure the namespace. The current solution consists in retracting into positives the structured type used in kat_completness, using denum.)

Definition sigma := positive.

the inductive type of regular expressions
Inductive regex :=
| r_zer
| r_one
| r_pls(e f: regex)
| r_dot(e f: regex)
| r_str(e: regex)
| r_var(a: sigma).

strict iteration is a derived operation
Definition r_itr e := r_dot e (r_str e).

inclusion into relational expressions
Fixpoint to_expr (e: regex): expr_(BKA) (fun _xH) (fun _xH) xH xH :=
  match e with
    | r_zer ⇒ 0
    | r_one ⇒ 1
    | r_pls e fto_expr e + to_expr f
    | r_dot e fto_expr e × to_expr f
    | r_str eto_expr e ^*
    | r_var ae_var a
  end.

Regular expressions form a Kleene algebra

Operations

we inherit the preorder and the equivalence relation from generic expressions
Definition r_leq e f := to_expr e <==_[BKA] to_expr f.
Definition r_weq e f := to_expr e ==_[BKA] to_expr f.

structures for regular expression operations
Canonical Structure regex_lattice_ops := {|
  car := regex;
  leq := r_leq;
  weq := r_weq;
  cup := r_pls;
  bot := r_zer;
  cap := assert_false r_pls;
  top := assert_false r_zer;
  neg := assert_false id
|}.

we use singleton type for the object(s), since this is a flat structure
CoInductive regex_unit := regex_tt.
Canonical Structure regex_ops := {|
  ob := regex_unit;
  mor n m := regex_lattice_ops;
  dot n m p := r_dot;
  one n := r_one;
  itr n := r_itr;
  str n := r_str;
  cnv n m := assert_false r_str;
  ldv n m p := assert_false r_dot;
  rdv n m p := assert_false r_dot
|}.

shorthand fore regex, when a morphism is required
Notation regex' := (regex_ops regex_tt regex_tt).
Definition var a: regex' := r_var a.

folding regular expressions to expose canonical preojections
Ltac fold_regex := ra_fold regex_ops regex_tt.

Laws

laws are inherited for free, by faithful embedding into general expressions

Instance regex_laws: laws BKA regex_ops.
Proof.
  apply (laws_of_faithful_functor (f:=fun _ _: regex_unitto_expr)).
  constructor; try discriminate; trivial.
  intros. constructor; try discriminate; trivial; now intros ???.
  intros. symmetry. apply itr_str_l.
  tauto. tauto.
Qed.

Instance regex_lattice_laws: lattice.laws BKA regex_lattice_ops.
Proof. exact (@lattice_laws _ _ regex_laws regex_tt regex_tt). Qed.

Predicates on regular expressions: 01, simple, pure

01 regular expressions are those not containing variables, they reduce either to 0 or to 1
Inductive is_01: regex' Prop :=
| is_01_zer: is_01 0
| is_01_one: is_01 1
| is_01_pls: e f, is_01 e is_01 f is_01 (e+f)
| is_01_dot: e f, is_01 e is_01 f is_01 (e×f)
| is_01_str: e, is_01 e is_01 (e^*).

simple regular expressions are those reducing to a sum of variables, possibly plus 1 (actually a bit less, since, e.g., 0*a×b reduces to 0 but is forbidden)
pure regular expressions are those without star, which reduce to a sum of variables (same thing as above)
ofbool produces 01 expressions
Lemma is_01_ofbool b: is_01 (ofbool b).
Proof. case b; constructor. Qed.

any 01 expression is simple
Lemma is_01_simple e: is_01 e is_simple e.
Proof. induction 1; now constructor. Qed.

Coalgebraic structure of regular expressions

epsilon membership

Fixpoint epsilon (e: regex') :=
  match e with
    | r_one
    | r_str _true
    | r_pls e fepsilon e || epsilon f
    | r_dot e fepsilon e && epsilon f
    | efalse
  end%bool.
Notation eps e := (@ofbool regex_ops regex_tt (epsilon e)).

derivatives

Fixpoint deriv a (e: regex'): regex' :=
match e with
  | r_zer | r_one ⇒ 0
  | r_pls e fderiv a e + deriv a f
  | r_dot e fderiv a e × f + eps e × deriv a f
  | r_str ederiv a e × (e: regex')^*
  | r_var bofbool (eqb_pos a b)
end.

word derivatives
Fixpoint derivs w e :=
  match w with
    | nile
    | cons a wderivs w (deriv a e)
  end.

set of variables appearing in a regular expression
Fixpoint vars (e: regex') :=
match e with
  | r_zer | r_onenil
  | r_pls e f | r_dot e fapp (vars e) (vars f)
  | r_str evars e
  | r_var acons a nil
end.

fundamental expansion theorem


Theorem expand' (e: regex') A: vars e <== A
  e == eps e + \sum_(a\in A) var a × deriv a e.
Proof.
  induction e; simpl vars; intro HA; simpl deriv; fold_regex.
  + rewrite sup_b, cupxb; ra.
  + rewrite sup_b, cupxb; ra.
  + apply cup_spec in HA as [HA1 HA2].
    simpl epsilon. setoid_rewrite orb_pls.
    setoid_rewrite dotxpls. rewrite supcup.
    rewrite IHe1 at 1 by assumption.
    rewrite IHe2 at 1 by assumption. simpl. fold_regex. ra.
  + apply cup_spec in HA as [HA1 HA2].
    setoid_rewrite dotxpls. rewrite supcup.
    rewrite IHe1 at 1 by assumption. rewrite dotplsx.
    rewrite IHe2 at 1 by assumption. rewrite dotxpls.
    rewrite dotxsum, dotsumx.
    simpl epsilon. rewrite andb_dot.
    setoid_rewrite dot_ofboolx. setoid_rewrite dotA.
    ra.
  + specialize (IHe HA). clear HA.
    simpl epsilon. setoid_rewrite dotA. rewrite <-dotsumx.
    set (f := \sum_(i\in A) var i × deriv i e) in ×. clearbody f.
    rewrite IHe. case epsilon; ra_normalise; rewrite ?str_pls1x; apply str_unfold_l.
  + setoid_rewrite cupbx. apply antisym.
    rewrite <- (leq_xsup _ _ a) by (apply HA; now left).
    rewrite eqb_refl. ra.
    apply leq_supx. intros b _. case eqb_spec; try intros <-; ra.
Qed.

Corollary expand e: e == eps e + \sup_(a\in vars e) var a × deriv a e.
Proof. apply expand'. reflexivity. Qed.

Corollary deriv_cancel a e: var a × deriv a e <== e.
Proof.
  rewrite (@expand' e ([a]++vars e)) at 2 by lattice.
  simpl. fold_regex. ra.
Qed.

monotonicity of epsilon

trick to prove that epsilon is monotone: show that it's an evaluation into the boolean KA
Lemma epsilon_eval e: epsilon e =
  eval (X:=bool_ops) (f':=fun _bool_tt) (fun _false) (to_expr e).
Proof. induction e; simpl; trivial; now rewrite IHe1, IHe2. Qed.

Instance epsilon_leq: Proper (leq ==> leq) epsilon.
Proof. intros e f H. rewrite 2epsilon_eval. apply H. apply lower_laws. Qed.
Instance epsilon_weq: Proper (weq ==> eq) epsilon := op_leq_weq_1.

monotonicity of derivation

we first need induction scheme for leq/weq

Definition re_ind leq weq := mk_ops regex_unit
  (fun _ _lattice.mk_ops regex' leq weq r_pls r_pls id r_zer r_zer)
  (fun _ _ _r_dot)
  (fun _r_one)
  (fun _r_itr)
  (fun _r_str)
  (fun _ _assert_false r_str)
  (fun _ _ _assert_false r_dot)
  (fun _ _ _assert_false r_dot).

Lemma re_ind_eval leq weq (e: regex'):
  eval (X:=re_ind leq weq) (f':=fun _regex_tt) var (to_expr e) = e.
Proof. induction e; simpl in *; reflexivity || congruence. Qed.

Lemma leq_ind leq weq (L: laws BKA (re_ind leq weq)) (e f: regex'): e <== f leq e f.
Proof.
  intro H. rewrite <-(re_ind_eval leq weq e), <-(re_ind_eval leq weq f). apply (H _ L).
Qed.

monotonicity of deriv
Instance deriv_leq a: Proper (leq ==> leq) (deriv a).
Proof.
  intros e f. apply (@leq_ind
  (fun e fe <== f deriv a e <== deriv a f)
  (fun e fe == f deriv a e == deriv a f)).
  constructor; simpl; (try discriminate); (repeat intros _); (repeat right);
    fold_regex; repeat intros _.
   constructor; simpl; (try discriminate); fold_regex; intros.
   - constructor. intro. split; reflexivity.
     intros ? ? ? [? ?] [? ?]; split; etransitivity; eassumption.
   - rewrite 2weq_spec. tauto.
   - rewrite 2cup_spec. tauto.
   - right. fold_regex. split; apply leq_bx.
   - split. apply dotA. rewrite andb_dot. ra.
   - split. apply dot1x. ra.
   - split. apply dotx1. ra.
   - intros x x' [Hx Hx'] y y' [Hy Hy']. split. now apply dot_leq.
     simpl; fold_regex. rewrite Hx', Hy', Hy. now rewrite Hx.
   - split. ra. rewrite orb_pls. ra.
   - split; ra.
   - split; ra.
   - split; ra.
   - split. apply str_refl. lattice.
   - split. apply str_cons. rewrite str_unfold_l. case epsilon; ra.
   - intros x z [H H']. split. now apply str_ind_l.
     apply str_ind_l in H. rewrite <-dotA, H, dot1x. hlattice.
   - intros x z [H H']. split. now apply str_ind_r.
     apply cup_spec in H' as [H1 H2]. rewrite dotA, H2. ra_normalise.
     now apply str_ind_r.
   - split. apply itr_str_l. reflexivity.
Qed.

Instance deriv_weq a: Proper (weq ==> weq) (deriv a) := op_leq_weq_1.

Instance derivs_leq w: Proper (leq ==> leq) (derivs w).
Proof. induction w; intros e f H. apply H. apply IHw, deriv_leq, H. Qed.

Instance derivs_weq w: Proper (weq ==> weq) (derivs w) := op_leq_weq_1.

deriving and expanding 01 regular expressions


Lemma deriv_01 a e: is_01 e deriv a e == 0.
Proof.
  induction 1; simpl deriv; fold_regex.
   reflexivity.
   reflexivity.
   rewrite IHis_01_1, IHis_01_2. apply cupI.
   rewrite IHis_01_1, IHis_01_2. ra.
   rewrite IHis_01. apply dot0x.
Qed.

Lemma expand_01 e: is_01 e e == eps e.
Proof.
  intro H. rewrite (expand e) at 1.
  rewrite sup_b. apply cupxb.
  intros. rewrite deriv_01 by assumption. apply dotx0.
Qed.

`pure part' of a regular expression


Fixpoint pure_part (e: regex'): regex' :=
  match e with
    | r_pls e fpure_part e + pure_part f
    | r_dot e feps e × pure_part f
    | r_str _ | r_one | r_zer ⇒ 0
    | r_var _e
  end.

Lemma is_pure_pure_part e: is_pure (pure_part e).
Proof. induction e; simpl pure_part; constructor; trivial. apply is_01_ofbool. Qed.

expanding simple regular expressions


Lemma str_eps e: eps e ^* == 1.
Proof. case epsilon. apply str1. apply str0. Qed.

Lemma expand_simple e: is_simple e e == eps e + pure_part e.
Proof.
  induction 1; simpl; fold_regex.
   lattice.
   lattice.
   lattice.
   rewrite orb_pls. rewrite IHis_simple1 at 1. rewrite IHis_simple2 at 1. lattice.
   rewrite andb_dot. rewrite (@expand_01 e) at 1 by assumption.
    rewrite IHis_simple at 1. ra.
   rewrite cupxb. rewrite (@expand_01 e) at 1 by assumption. apply str_eps.
Qed.

epsilon, derivatives, and expansion of pure regular expressions


Lemma epsilon_pure e: is_pure e epsilon e = false.
Proof.
  induction 1; trivial. simpl.
  now rewrite IHis_pure1.
  simpl. rewrite IHis_pure. now case epsilon.
Qed.

Lemma epsilon_deriv_pure a e: is_pure e eps (deriv a e) == deriv a e.
Proof.
  induction 1; simpl; fold_regex.
  reflexivity.
  rewrite <-expand_01. reflexivity. apply is_01_ofbool.
  rewrite orb_pls. now apply cup_weq.
  rewrite orb_pls, 2andb_dot, IHis_pure.
  rewrite deriv_01 by assumption. case (epsilon e); simpl; fold_regex; ra.
Qed.

Lemma expand_pure e A: is_pure e vars e <== A e == \sum_(a \in A) var a × deriv a e .
Proof.
  intros He HA. rewrite (expand' e HA) at 1.
  rewrite epsilon_pure by assumption. apply cupbx.
Qed.

additional properties

Lemma deriv_sup a I J (f: I regex'):
  deriv a (\sup_(i\in J) f i) = \sup_(i\in J) deriv a (f i).
Proof. apply f_sup_eq; now f_equal. Qed.

Lemma epsilon_reflexive e: epsilon e 1 <== e.
Proof. intro H. rewrite (expand e), H. lattice. Qed.

Language interpretation of regular expressions

language of a regular expression, coalgebraically


Definition lang e: lang' sigma := fun wepsilon (derivs w e).

Instance lang_leq: Proper (leq ==> leq) lang.
Proof. intros e f H w. unfold lang. now rewrite H. Qed.

Instance lang_weq: Proper (weq ==> weq) lang := op_leq_weq_1.

(internal) characterisation of epsilon
Lemma epsilon_iff_reflexive_eps (e: regex'): epsilon e 1 <== eps e.
Proof.
  case epsilon. intuition. intuition. discriminate.
  apply lang_leq in H. specialize (H [] eq_refl). discriminate.
Qed.

lang is a KA morphism

to prove that lang is a morphism, we characterise it inductively, as the unique morphism such that lang (e_var i) is the language reduced to the letter i, (eq [i])

Notation elang e := (eval (f':=fun _lang_tt) (fun ieq [i]) (to_expr e)).

language characterisation of epsilon
Lemma epsilon_iff_lang_nil e: epsilon e (elang e) [].
Proof.
 induction e; simpl.
  firstorder discriminate.
  firstorder.
  setoid_rewrite Bool.orb_true_iff. now apply cup_weq.
  setoid_rewrite Bool.andb_true_iff. setoid_rewrite lang_dot_nil. now apply cap_weq.
  split. now O. reflexivity.
  firstorder discriminate.
Qed.

regular expression derivatives precisely correspond to language derivatives
Lemma eval_deriv a e: elang (deriv a e) == lang_deriv a (elang e).
Proof.
  induction e; simpl deriv; simpl eval; fold_regex; fold_lang.
  - reflexivity.
  - now rewrite lang_deriv_1.
  - rewrite lang_deriv_pls. now apply cup_weq.
  - generalize (epsilon_iff_lang_nil e1). case epsilon; intro He1.
     setoid_rewrite dot1x.
     setoid_rewrite lang_deriv_dot_1. 2: now apply He1.
     now rewrite <- IHe1, <- IHe2.
     setoid_rewrite dot0x.
     setoid_rewrite lang_deriv_dot_2. 2: clear -He1; intuition discriminate.
     rewrite <- IHe1. apply cupxb.
  - rewrite lang_deriv_str. now rewrite <- IHe.
  - case eqb_spec. intros <- w. compute. split. now intros <-. now intro E; injection E.
    intros D w. compute. split. intros []. intro E. apply D. injection E. congruence.
Qed.

we deduce that both notions of language coincide: lang is the unique morphism from the coalgebra of regular expressions to the final coalgebra of languages
Theorem lang_eval e: lang e == elang e.
Proof.
  unfold lang. intro w. revert e. induction w as [|a w IH]; intro e; simpl derivs.
  - apply epsilon_iff_lang_nil.
  - rewrite IH. apply eval_deriv.
Qed.

as a consequence, lang is a KA morphism
Corollary lang_0: lang 0 == bot.
Proof. now rewrite lang_eval. Qed.

Corollary lang_1: lang 1 == 1.
Proof. now rewrite lang_eval. Qed.

Corollary lang_var i: lang (var i) == eq [i].
Proof. now rewrite lang_eval. Qed.

Corollary lang_pls e f: lang (e+f) == lang e \cup lang f.
Proof. now rewrite 3lang_eval. Qed.

Corollary lang_sup I J (f: I _): lang (sup f J) == \sup_(i\in J) lang (f i).
Proof. apply f_sup_weq. apply lang_0. apply lang_pls. Qed.

Corollary lang_dot e f: lang (e×f) == lang e × lang f.
Proof. now rewrite 3lang_eval. Qed.

Corollary lang_itr e: lang (e^+) == lang e^+.
Proof. rewrite 2lang_eval. simpl (elang _). symmetry. apply itr_str_l. Qed.